Effect of hydrothermal pretreatment severity on lignin inhibition in enzymatic hydrolysis. (May 2019) - Kellock, Miriam; Maaheimo, Hannu; Marjamaa, Kaisa; Rahikainen, Jenni; Zhang, Heng; Holopainen-Mantila, Ulla; Ralph, John; Tamminen, Tarja; Felby, Claus; Kruus, Kristiina
Highlights: Lignin inhibition in enzymatic hydrolysis was induced by pretreatment. Lignin inhibition in Avicel hydrolysis correlated with the combined severity factor. At same pretreatment severities wheat straw and spruce lignin were equally inhibitory. Abstract: Hydrothermal pretreatment is commonly used for enhancing enzymatic hydrolysis of lignocellulosics. Spruce and wheat straw were pretreated with increasing severity and lignin characteristics were analysed. The effect of enzymatically isolated lignin on the hydrolysis of Avicel and the adsorption of a cellobiohydrolase onto lignin was measured. Non-pretreated lignins had only a minor effect on Avicel hydrolysis. The structural changes in lignin accompanying hydrothermal pretreatment were associated with increased binding and inactivation of the cellulase on the lignin surface. The inhibitory effect was more pronounced in spruce than in wheat straw lignin. However, similar pretreatment severities caused similar levels of inhibition in Avicel hydrolysis for both biomass sources. The combined severity factor of the pretreatment correlated well with the inhibitory effect of lignin.